Iran’s Arak Heavy Water Reactors: Past, Present and Future - Debalina Ghoshal (International Journal of Nuclear Security, 2018)
The Iranian nuclear impasse involved issues related to centrifuges and uranium enrichment, the Fordow underground enrichment plant and the IR-40 Heavy Water Reactors (HWRs). It is in this context that the paper tracks the development of the Arak HWRs prior to the nuclear deal and the concerns regarding the HWRs during the nuclear negotiation process and the neutering process post Joint Comprehensive Plan of Action (JCPOA). The paper further discusses whether Iran could resort to nuclear weapons with either enriched uranium or HWRs.